The Kalhora Dynasty: A Period of Islamic Architecture, From the Early Throne to the Present. - Rabia Khaskheli; Mazhar Hussain Abbasi (Sir Syed University Research Journal of Engineering and Technology, 2024)
Since the architecture of the Kalhora period has long piqued the curiosity of academics, a number of works have been published examining the evolution of the style and its persistence in the region. The Mughals were retreating from most parts of the subcontinent as disturbances began to appear on the political scene in Sindh. However, during the Mughal and Kalhora periods, the methods of decorative art and architecture were essentially the same. On the other hand, buildings of the Kalhora period lack such evidence, which is generally present to varying degrees in buildings of other periods in Sindh. Here, an attempt has been made to see how the various phases of architectural architecture during the Kalhora rule influenced other spheres of life. Along with the history of the Kalhora rule, the various stages of development of mosques and tomb architecture are also discussed, along with the new architectural features added by the Kalhoras and other patterns much admired in Indian architecture. One of its aims is to provide data on the archaeological architecture of the Indus and to be helpful to students studying archeology. Local patterns related to the construction of publications are ignored. This paper aims to address the knowledge gap about local architecture.